2017
DOI: 10.1080/1828051x.2017.1321473
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of sexed versus conventional semen in Holstein heifers in various semiarid regions of Iran

Abstract: For comparing reproductive performance of sexed versus conventional semen a total of 3573 heifer insemination records collected from five herds in four provinces of Iran were investigated. The studied provinces were classified into three regions: hot semiarid (Tehran and Alborz provinces), temperate semiarid (Khorasan Razavi province) and cold semiarid (Zanjan province). Various parameters including the conception rate, number of services per conception, calf sex ratio, calf birth weight, gestation length, cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
(53 reference statements)
1
3
0
Order By: Relevance
“…Another study, performed by Seidel and Schenk (2008) [ 83 ], showed lower pregnancy rates from using sex-sorted semen as compared to non-sorted. The abovementioned findings are corroborated with more recent research carried out by Mikkopla et al (2015), [ 84 ], Joezy-Shekalgorabi et al (2017) [ 85 ], Dawod and Elbaz (2020) [ 81 ], and Drake et al (2020) [ 86 ] regarding the reproductive efficiency of sex-sorted sperm in cows and heifers. However, when determining whether or not to use sex-sorted semen in a dairy farm, the climatic and management practices of a herd in a particular environment must be taken into account.…”
Section: Conventional and Sex-sorted Semen Market—present And Future Trendssupporting
confidence: 83%
“…Another study, performed by Seidel and Schenk (2008) [ 83 ], showed lower pregnancy rates from using sex-sorted semen as compared to non-sorted. The abovementioned findings are corroborated with more recent research carried out by Mikkopla et al (2015), [ 84 ], Joezy-Shekalgorabi et al (2017) [ 85 ], Dawod and Elbaz (2020) [ 81 ], and Drake et al (2020) [ 86 ] regarding the reproductive efficiency of sex-sorted sperm in cows and heifers. However, when determining whether or not to use sex-sorted semen in a dairy farm, the climatic and management practices of a herd in a particular environment must be taken into account.…”
Section: Conventional and Sex-sorted Semen Market—present And Future Trendssupporting
confidence: 83%
“…From an economic point of view, embryo transplantation is especially interesting for commercial farms that do not have breeding animals, but intend to create a breeding nucleus of cattle. For such agricultural enterprises, it is enough to have a broodstock -recipients (outbreds), to whom embryos can be transplanted [30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, cattle-sexed semen has a fertility rate of 71.5% to 78.5% that of whole semen [ 60 ]. Though these reduced rates are acceptable for dairy producers and some beef producers to use sexed semen, fertility rates are still the foremost issue facing sexed semen.…”
Section: Sperm Sexingmentioning
confidence: 99%